PENGARUH METODE PEMBELAJARAN GRUP INVESTIGASI DALAM MENELAAH UNSUR-UNSUR DAN CIRI BAHASA SERTA MENULIS SURAT PRIBADI - Ifham Darussalam; Cecep Najimudin; Dida Firmansyah (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2019)
The study was conducted to determine the significant influence of the Investigation Group method of learning to know the ability to examine and write personal letters. The research method used is experimental method with pretest and posttest group design. The hypothesis proposed in this study can be proved true, because the hypothesis is applied using the statistical test turns out the average value of the students' experimental class ability in reviewing and writing personal letters using the Investigation Group method. The Investigative Group method significantly influences the ability to examine the elements and traits of the language as well as personal letter writing, it can be proved by the activeness of the students who use the Investigation Group method and can encourage and be creative in the students themselves.